O design de aparência de atores e a comunicação em cena - Ramos, Adriana Vaz (2008)
This study aimed to analyze the actor s visual characterization, which is the language used to construct the actor s and characters appearance for performances, as well as to evaluate its importance for the construction of signs in a particular artistic production. Visual characterization specifically refers to the expressive relationships among colors, shapes, volumes and lines that differently from the costumes, makeup, hairdo and accessories in order to translate the general appearance into sensitive plastic material, that is, the actor s characterization in a production scene. Nowadays, in performances broadcasted by different means, a distinct manner to conceive the construction of the actor s appearance has been noted. It differs from the simple reference functions that are usually presented by the concept of costume design in a production, generally considered an accessory of the representation. A costume design production results from a mimetic referential design that anticipates the performance where the actor is inserted, like costumes portraying a determined period in time, for example. This study reflects on the complexity process that the language named actor s visual characterization has been going through, in order to understand its conceptual field and propose the existence of another way to constitute this language defined as actor s appearance design, where the costume design is just a partial element. As a language, visual characterization may be organized according to costume design or appearance design. Giulio Carlo Argan s concepts of existing differences between project and program as well as Regis Debray s propositions of distinct ways to organize a piece of information were decisive to define the concept of appearance design and show the divergences between the actor s characterization form and the costume design production. Because of the metonymic mechanism of thinking, common sense uses the word costume to refer to an actor s general appearance, ignoring the importance of the other components to the construction of the scenic image. The concepts elaborated by the semioticians from the Tartu- Moscow School present the necessary theoretical perspectives to the understanding of the actor s appearance in performances with open systems that consist of dialogues among several modeling systems. Therefore, it can be said that an actor s appearance is a cultural text, which resulted from a complex overlapping of languages, and that can only be understood through that complexity. An artistic performance is a systemic production, a bundle of relations, in which innumerous languages influence the construction of the final product. It is not possible to isolate just one of the constituting languages of a production in order to understand it because it is always necessary to do a relational reading, mainly a communicating or mediating one, of the inference repertoire that may be constructed by the receptor. The realized analyses try to understand how the images created by the actor s appearance design construct spatialities in an artistic scene. Thus, the following analytical corpus was studied: Os sete gatinhos, a play by Nelson Rodrigues, directed by Antunes Filho in 1989; the micro series Hoje é dia de Maria, directed by Luiz Fernando Carvalho and produced by Globo Television Network in 2005; and three images made by the American photographer Cindy Sherman